1974
DOI: 10.2134/agronj1974.00021962006600010028x
|View full text |Cite
|
Sign up to set email alerts
|

Hail Damage to Upland Cotton1

Abstract: There has been very little scientific data published on the effect of hail damage on Upland cotton (Gossypium hirsutum L.) because of the nature of the problem and difficulty in setting up an appropriate, experimentally sound investigation. A hailstorm on June 26, 1971 made it possible to collect data on the effect of differential damage to individual Upland cotton plants. Three injury classes were established: 1) slight — some stem and leaf damage; 2) moderate — terminal bud lost plus some leaf and stem damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…Lint turnout was affected when damage occurred at greater intensity at early‐season timings. These results agree with the findings of Peacock and Hawkins (1974), who found that plants severely injured early in the season had less lint turnout than plants with no injury or moderate injury. However, Smith and Varvil (1981) conducted research that did not observe any differences in lint turnout regardless of damage.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Lint turnout was affected when damage occurred at greater intensity at early‐season timings. These results agree with the findings of Peacock and Hawkins (1974), who found that plants severely injured early in the season had less lint turnout than plants with no injury or moderate injury. However, Smith and Varvil (1981) conducted research that did not observe any differences in lint turnout regardless of damage.…”
Section: Resultssupporting
confidence: 92%
“…No differences in micronaire were observed when damage occurred at first bloom or first bloom + 4 wk regardless of damage intensity. Similar findings were reported by Peacock and Hawkins (1974) as well as Smith and Varvil (1981) who found micronaire decreased as damage intensity increased. However, while differences in micronaire were observed, they did not affect price discount.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, hail storm could also damage terminal buds, causing severe yield loss in cotton. For example, in an assessment of five cotton cultivars after a natural hail storm, Peacock and Hawkins (1974) found that terminal bud loss at the early growth stage accounted for 39 % yield reduction. In contrast, manual excising of plant growing tips/terminal buds before squaring in Australia resulted in increased yields owing to a significant increase in lateral branch growth that later contributed to a higher fruiting potential and increased light interception (Lei and Gaff 2003).…”
Section: Introductionmentioning
confidence: 99%